2012
DOI: 10.1007/s13204-012-0078-8
|View full text |Cite
|
Sign up to set email alerts
|

An alternative improved method for the homogeneous dispersion of CNTs in Cu matrix for the fabrication of Cu/CNTs composites

Abstract: Copper has a wide range of applications due to its excellent properties (high thermal and electrical conductivity). Carbon nanotubes (CNTs) are widely used as a reinforcing material due to their superior properties. Copper/Carbon nanotube (Cu/CNTs) composites show enhanced mechanical, electrical and thermal properties as compared to pure Cu and Cu composites. Hence, Cu/CNTs composites have tremendous applications. Cu/CNTs are being developed for use as antifungal and antimicrobial agents, which can lead to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Considering that commercial CNTs are usually delivered in agglomerated form, different methods have to be employed to disaggregate and blend them with the metallic matrix material. There are a lot of dispersing and blending processes like magnetic stirring [40], nanoscale dispersion processing [18,21,41], colloidal mixing [6,16,22,[26][27][28][29][30][31][41][42][43][44][45][46][47][48][49], molecularlevel mixing [7,9,11,12,14,24,25,[50][51][52][53][54], particle composite system mixing [15,55], friction stir processing [56], layer stacking [57], ball milling [8,10,17,19,20,[22][23][24][32]…”
Section: Blending Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that commercial CNTs are usually delivered in agglomerated form, different methods have to be employed to disaggregate and blend them with the metallic matrix material. There are a lot of dispersing and blending processes like magnetic stirring [40], nanoscale dispersion processing [18,21,41], colloidal mixing [6,16,22,[26][27][28][29][30][31][41][42][43][44][45][46][47][48][49], molecularlevel mixing [7,9,11,12,14,24,25,[50][51][52][53][54], particle composite system mixing [15,55], friction stir processing [56], layer stacking [57], ball milling [8,10,17,19,20,[22][23][24][32]…”
Section: Blending Methodsmentioning
confidence: 99%
“…Using low energy ball milling, this unwanted effect can be reduced, but it will not vanish. The importance of a low defect density of CNTs will be discussed later on in entry 2.2 [8,10,17,19,20,[22][23][24][32][33][34][35][36]38,50,53,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74].…”
Section: Ball Millingmentioning
confidence: 99%
“…The optimum sintering temperature and time for MMCs based on copper reinforced CNT were reported at 900 °C and 2 h, by previous researches [22,[42][43][44]. Therefore, in this work, conventional sintering process was carried out at a sintering temperature of 900 °C for 2 h, and the samples produced by microwave sintering method was selected for 20 min sintering time.…”
Section: (A) (B) (C)mentioning
confidence: 99%
“…A broad range of studies have reported that CNTs improve the performance of ceramic and polymer matrix in the last decades [14][15], and researches on metal matrices reinforced with CNTs are to some extent restricted [16]. The main issue in the synthesis of metal-CNTs nanocomposites is to achieve a homogeneous dispersion of CNT powders in the metallic matrices [1][2][16][17]. However, many research groups have employed efficient methods to enhance dispersion.…”
Section: Introductionmentioning
confidence: 99%